2020
DOI: 10.1007/s10388-020-00772-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic significance of serum inflammatory markers in esophageal cancer

Abstract: Background The aim of this study was to assess the relative prognostic value of biomarkers to measure the systemic inflammatory response (SIR) and potentially improve prognostic modeling in patients undergoing potentially curative surgery for esophageal adenocarcinoma (EC). Methods Consecutive 330 patients undergoing surgery for EC between 2004 and 2018 within a regional UK cancer network were identified. Serum measurements of haemoglobin, C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…The role of inflammatory mediators, including C-reactive protein and neutrophil-to-lymphocyte ratio, on cancer recurrence has also been evaluated in patients with esophageal cancer. 26 Powell and colleagues 26 found that inflammatory mediators were independently associated with worse overall and diseasefree survival for patients undergoing esophagectomy with curative intent. In a recent systematic review of 17 569 patients who had developed recurrence following breast cancer surgery, 2077 patients were found to have a concomitant surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammatory mediators, including C-reactive protein and neutrophil-to-lymphocyte ratio, on cancer recurrence has also been evaluated in patients with esophageal cancer. 26 Powell and colleagues 26 found that inflammatory mediators were independently associated with worse overall and diseasefree survival for patients undergoing esophagectomy with curative intent. In a recent systematic review of 17 569 patients who had developed recurrence following breast cancer surgery, 2077 patients were found to have a concomitant surgical site infection.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the inflammation marker, NLR is used as a prognostic factor in cancers. Higher pretreatment NLR is correlated with worse OS in oropharyngeal cancer treated and worse disease-free survival and OS in esophageal cancer with radiotherapy [ 47 , 48 , 49 ]. High post-RT NLR is associated with poor OS and PFS in nasopharyngeal cancer and higher recurrent rate in breast cancer [ 39 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which a low PNI decreases the survival time of patients with BC has not been fully elucidated. The PNI is based on lymphocyte count and albumin level, which are significantly closely related to the prognosis of cancer patients [ 30 ], and a low PNI indicates increased inflammatory reaction and poor nutritional status [ 31 ]. Prior study reported that BC patients with higher serum albumin showed 45% reduced risk of death (HR = 0.55, 95% CI: 0.40–0.75) than those with lower albumin level, indicating that albumin could be an independent predictor of prognosis of BC patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%